Controlling interfacial interactions of supramolecular assemblies by light-responsive overcrowded alkenes. Issue 69 (9th August 2019) - Shi, Zhao-Tao; Yu, Jing-Jing; Zhang, Qi; Li, Ming-Ming; Liang, Wen-Jing; Zhao, Cai-Xin; Qu, Da-Hui
Abstract : Controlled interfacial interactions of supramolecular assemblies are achieved by effective photo-isomerization of the overcrowded alkene units. Abstract : A light-responsive supramolecular polymer was constructed by an AB-type monomer containing a light-responsive overcrowded alkene. The primary assemblies of the supramolecular polymer can further undertake secondary self-assembly by interfacial host–guest connections, which can be manipulated by light stimuli to convert into discrete primary assemblies.